Semiotic study of the meaning of Evaluasi song lyrics from Hindia - Mubarok, Mubarok; Pradana, Arsil Bayu; Triyono, Agus; Mulyadi, Urip (Journal of Advanced Multidisciplinary Research, 2023)
This research was motivated by the problem of how the song Evaluasi popularized by Hindia (Baskara Putra) was released in March 2019 which raised the issue of mental health problems, namely overthinkers. Music is used as a means to reach the masses by using it as a message or simply for entertainment by the listeners, but music is listened to not only for pleasure, but music is also able to have an influence on thoughts and emotions, especially mood. The aim of this research is to find out the meaning of Sign, Object and Interpretant as presented in the lyrics of the song Evaluasi popularized by Hindia (Baskara Putra). The research method used in this research is a qualitative descriptive approach with data collection techniques through observation, documentation, and literature study. The paradigm in this research uses a critical paradigm. The results of this research show that the lyrics contained in the song Evaluasi by Hindia are known to have levels of meaning Sign, Object and Interpretant. The results explains that mental health is important even as important as physical health. This Evaluasi song emphasizes the importance of Self Awareness accompanied by positive suggestions. The limitation of this research is that there is still a lack of discussion about mental health problems, so the recommendation that needs to be made for further research is to develop similar research using a different paradigm in order to find novelty in the research results.